Crystal-Quasichemical Analysis of Defect Subsystem of Doped PbTe: Sb Crystals and Pb-Sb-Te Solid Solutions - Freik, D.M.; Turovska, L.V. (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
Within crystalquasichemical formalism models of point defects of crystals in the Pb-Sb-Te system were specified. Based on proposed crystalquasichemical formulae of antimony doped crystals PbTe:Sb amphoteric dopant effect was explained. Mechanisms of solid solution formation for РbТе-Sb2Те3: replacement of antimony ions lead sites with the formation of cation vacancies (I) or neutral interstitial tellurium atoms (II) were examined. Dominant point defects in doped crystals PbTe:Sb and РbТе-Sb2Те3 solid solutions based on p-PbTe were defined. Dependences of concentration of dominant point defects, current carriers and Hall concentration on content of dopant compound and the initial deviation from stoichiometry in the basic matrix were calculated.